2010
DOI: 10.4193/rhin09.144
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled trial of anti-IgE for chronic rhinosinusitis

Abstract: Evidence suggests IgE may play a role in chronic rhinosinusitis (CRS). We sought to determine if treatment with a monoclonal antibody against IgE (omalizumab) is effective in reducing CRS inflammation. We performed a randomized, double blind, placebo controlled clinical trial in subjects with CRS despite treatment (including surgery). Subjects were randomized to receive omalizumab or placebo for 6 months. The primary outcome was quantitative measurement of sinus inflammation on imaging. Secondary outcome measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
170
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(183 citation statements)
references
References 0 publications
7
170
1
5
Order By: Relevance
“…Concerning omalizumab, Pinto et al (19) did not manage to show any significant change in TPS in the treatment as compared to placebo group (p<0,58). On the contrary, Gevaert et al (21) demonstrated that the treatment with omalizumab resulted in significant reduction in TPS compared to placebo (p=0,01 and p=0,99, respectively).…”
Section: Literature Searchmentioning
confidence: 88%
See 3 more Smart Citations
“…Concerning omalizumab, Pinto et al (19) did not manage to show any significant change in TPS in the treatment as compared to placebo group (p<0,58). On the contrary, Gevaert et al (21) demonstrated that the treatment with omalizumab resulted in significant reduction in TPS compared to placebo (p=0,01 and p=0,99, respectively).…”
Section: Literature Searchmentioning
confidence: 88%
“…Six studies fulfilled the inclusion criteria (18)(19)(20)(21)(22)(23) . Αll studies were RCTs and were published between 2006 and 2017.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous double-blind, randomized, placebo-controlled trial by Pinto et al [15] studied omalizumab in a cohort of subjects with CRS with prior sinus surgery, most presenting with polyps; the trial resulted in a statistically significant decrease in sinus CT scan involvement (accompanied by a reduced need for steroid therapy) that was not confirmed when the magnitude of change was compared across groups. Moreover, none of the other secondary outcomes were not successfully reached.…”
Section: Monoclonal Antibodies In Crswnpmentioning
confidence: 99%